The Relationship Between Emotional Maturity and Aggressiveness in the Football Supporters Group in Sidoarjo: Hubungan Antara Kematangan Emosional dengan Agresivitas pada Kelompok Suporter Sepakbola di Sidoarjo - Ulumudin, Ristananda Nova Ihya; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
Recently, cases about the aggressiveness of football fans are increasingly being reported in the mass media. Emotional maturity is one of the factors that triggers the emergence of aggressiveness in football fans. The purpose of this study was to determine the relationship between emotional maturity and aggressiveness in the football supporters group X in Gedangan sub-district. This study uses a correlational quantitative approach. In this study used a sample of 108 people obtained from sampling using purposive sampling technique. The data collection technique was carried out using the aggressiveness scale and emotional maturity scale, which were compiled using a Likert scale. The data were analyzed by testing the hypothesis using the Pearson Correlation Product Moment with the help of the SPSS v.19 for windows program. The results showed a correlation coefficient of -.961 (significant. 0.000 <0.05). Thus, the research hypothesis is accepted, that there is a significant negative relationship between emotional maturity and aggressiveness in the football supporters group X in Gedangan sub-district. A person's high emotional maturity will have an impact on low aggressiveness. Conversely, a person's low emotional maturity will result in an increase in aggressiveness. In addition, it is known that half of all X football supporters in Gedangan sub-district (52.8%) have low emotional maturity. Meanwhile, in terms of aggressiveness, half of all X football supporters in Gedangan sub-district (54.6%) show high aggressiveness. . Meanwhile, the results of the coefficient of determination test show that the emotional maturity variable has an influence of 77.5% on the aggressive behavior variable.